A Case Report of Hypoglycemia Following a Tramadol Overdose in a Non-Diabetic Patient. (August 2022) - Weant, Kyle A.; Clendening, Alexander M.; Bush, Jeffrey S.
Introduction: Tramadol is an opioid analgesic that binds to mu-opioid receptors and inhibits the uptake of norepinephrine and serotonin. Through its activation of these receptors, it has potential to increase the utilization of glucose and/or decrease hepatic gluconeogenesis. Case Report: A 55-year-old male presents to the Emergency Department (ED) via Emergency Medical Services (EMS) following a self-reported overdose of alprazolam, lorazepam, acetaminophen with codeine, and tramadol. During EMS transport, the patient was found to be hypoglycemic with a glucose of 30 mg/dL and was administered 25 grams of intravenous (IV) dextrose 50% in water. The patient had no past medical history of diabetes mellitus, hypoglycemia, or hyperglycemia and was normoglycemic on his prior presentations to our facility 3 months and 2 years prior. Subsequent analysis found that the patient was negative for acetaminophen, ethanol, salicylates, tricyclics, and lithium. His urinalysis was positive for opiates and benzodiazepines. Upon arrival to the ED, the patient's blood glucose was 131 mg/dL but subsequently dropped to 73 mg/dL, necessitating the initiation of continuous IV fluids containing dextrose. These fluids were discontinued 3.5 hrs later and the patient was discharged 16 days later. Discussion: This case illustrates that hypoglycemia can be a presenting symptom in patients with an acute overdose of tramadol with no previous history of glycemic dysregulation. Upon presentation it is important to closely monitor serum glucose concentrations to identify hypoglycemia early in order to initiate necessary hypoglycemia protocols.